Formal syntheses of (2R,3R)-3-hydroxy pipecolic acid and (2R,3S)-3-hydroxy pipecolic acid from L-ascorbic acid - Chavan, Subhash P.; Dumare, Nilesh B.; Pawar, Kailash P. (Tetrahedron Letters, 2015)
Formal syntheses of both cis and trans 3-hydroxy pipecolic acids is achieved from L-ascorbic acid. Present synthesis describes use of chiral pool approach in which epimerization, Staudinger reaction and Cyclization reactions were employed as key steps. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: 3-Hydroxy pipecolic acid; cyclization; Epimerization; L-Ascorbic acid

Formal Synthesis of Corynanthe Indole Alkaloid (±)-Mitralactonine: Construction of α-Hydroxy-Keto Functionalized Tetracyclic Skeleton - Dumare, Nilesh B.; Sharma, Pallavi; Sivappa, Rasapalli; Chavan, Subhash P. (Chemistryselect, 2025)
An efficient synthesis of a tetracyclic skeleton common to many corynanthe alkaloids was accomplished in 10 linear steps starting from a known tetrahydro beta-carboline intermediate. The tetracyclic alpha-hydroxy keto functionalized advanced precursor of (+/-)-mitralactonine was realized using Wittig olefination, ketohydroxylation of a trisubstituted alkene, and a tandem amine unmasking-intramolecular nucleophilic displacement reaction for C-N bond formation of C/D-rings.
Keywords: alpha-hydroxy keto; beta-carboline; corynanthe alkaloid; intramolecular N-alkylation; mitragynine